2021
DOI: 10.1212/wnl.0000000000012148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Disability Associated With Head Injury With Loss of Consciousness in Adults in the United States

Abstract: Objective:To provide nationally representative prevalence estimates of disability associated with prior head injury with loss of consciousness in the U.S. and to examine associations between prior head injury and disability.Methods:Cross-sectional analysis of 7,390 participants aged ≥40 years in the 2011-2014 National Health and Nutrition Examination Surveys (NHANES). Head injury with loss of consciousness was assessed by self-report. Domains of disability were assessed using a standardized structured question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…More than 2.5 million new cases of traumatic brain injury (TBI) are diagnosed annually in the U.S. and an estimated 11 million individuals are living with long-term TBI-associated disability [ 1 , 2 ]. Epidemiological studies have demonstrated an association between TBI exposure(s) and an increased risk of age-related neurocognitive decline or dementia [ 3 - 7 ], including a 2018 retrospective cohort study involving over 350,000 military veterans which found more than a two-fold increased risk of developing dementia amongst individuals with mild TBI exposure and more than a 3.5-fold increased risk of developing dementia amongst individuals with moderate-to-severe TBI exposure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 2.5 million new cases of traumatic brain injury (TBI) are diagnosed annually in the U.S. and an estimated 11 million individuals are living with long-term TBI-associated disability [ 1 , 2 ]. Epidemiological studies have demonstrated an association between TBI exposure(s) and an increased risk of age-related neurocognitive decline or dementia [ 3 - 7 ], including a 2018 retrospective cohort study involving over 350,000 military veterans which found more than a two-fold increased risk of developing dementia amongst individuals with mild TBI exposure and more than a 3.5-fold increased risk of developing dementia amongst individuals with moderate-to-severe TBI exposure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has magnified these longstanding inequities [ 11 ]; persons with disabilities are at higher risk of serious illness secondary to underlying neurologic conditions [ 12 , 13 ] and have more difficulty engaging in COVID-19 preventative measures [ 14 ]. Persons with traumatic brain injury (TBI) represent an estimated 11.4 million persons with disability [ 15 ] who may be particularly affected by the pandemic, though currently only one cross-sectional study exists on how the COVID-19 pandemic has affected TBI survivors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Persons with acquired brain injury (pwABI), due to either stroke or trauma, can experience long term changes in participation across multiple facets of life (1)(2)(3)(4)(5)(6). Acquired brain injury (ABI) has been found to result in a higher prevalence of disability when compared to the general population (7), and to result in long-term impacts on daily function (8). Helping pwABI engage in valued tasks and roles is a goal shared by pwABI, their families, clinicians, and researchers (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%